Urinary Bisphenol A and Hypertension in a Multiethnic Sample of US Adults. (27th January 2012) - Shankar, Anoop; Teppala, Srinivas
Abstract : Background . Bisphenol A (BPA) is a common chemical used in the manufacture of polycarbonate plastics and epoxy resins, with >93% of US adults having detectable BPA levels in urine. Recent animal studies have suggested that BPA exposure may have a role in several mechanisms involved in the development of hypertension, including weight gain, insulin resistance, thyroid dysfunction, endothelial dysfunction, and oxidative stress. However, no previous human study has examined the association between markers of BPA exposure and hypertension. Methods . We examined urinary BPA levels in 1380 subjects from the National Health and Nutritional Examination Survey 2003-2004. Main outcome-of-interest was hypertension, defined as blood pressure-reducing medication use and/or blood pressures >140/90 mm of Hg (n = 580 ). Results . We observed a positive association between increasing levels of urinary BPA and hypertension independent of confounding factors such as age, gender, race/ethnicity, smoking, body mass index (BMI), diabetes mellitus and total serum cholesterol levels. Compared to tertile 1 (referent), the multivariate-adjusted odds ratio (95% confidence interval) of hypertension associated with tertile 3 was 1.50 (1.12−2.00); P -trend = 0.007. The association was consistently present in subgroup analyses by race/ethnicity, smoking status, BMI, and diabetes mellitus. Conclusions . Urinary BPA levels are associated with hypertension, independent of traditional risk factors.